Positive electrode active material, method of preparing the same, and rechargeable lithium battery comprising the same

CN116799195BActive Publication Date: 2026-10-30SAMSUNG SDI CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211650899.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-03-22
Filing Date
2022-12-21
Publication Date
2026-10-30
Estimated Expiration
2042-12-21

AI Technical Summary

Technical Problem

当使用这种正极活性物质时,随着重复充电和放电由于在正极活性物质中生成的裂纹,降低了正极活性物质的长期循环寿命,增加了其电阻,并且容量特点未达到令人满意的水平,并且因此需要改善

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116799195B_ABST
    Figure CN116799195B_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material, a method of preparing the same, and a rechargeable lithium battery including the same. The positive electrode active material for a rechargeable lithium battery includes a lithium nickel-based composite oxide, wherein the positive electrode active material is in the form of secondary particles in which a plurality of primary particles are aggregated and at least a portion of the primary particles are radially arranged, the secondary particle includes an inner portion and an outer portion, the inner portion of the secondary particle is a region surrounded by a point at a length of 50±5% of a total distance from a center of the secondary particle to a surface of the secondary particle from the center of the secondary particle, and is a region in which the primary particles and pores are irregularly arranged, and the outer portion of the secondary particle is a region surrounding the inner portion, in which at least a portion of the primary particles are radially arranged in the outer portion, and the number ratio of the primary particles having an aspect ratio greater than or equal to 4 in the outer portion of the secondary particle is greater than or equal to 18%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] A positive electrode active material for a rechargeable lithium battery, a method for preparing the same, and a rechargeable lithium battery including the same are disclosed. Background Technology

[0002] Portable information devices such as mobile phones, laptops, and smartphones, as well as electric vehicles, already use rechargeable lithium batteries with high energy density and portability as their power source. Recently, research has been actively underway to use rechargeable lithium batteries with high energy density as a power source or energy storage source for hybrid or electric vehicles.

[0003] As the positive electrode active material for rechargeable lithium batteries, lithium nickel oxides, such as lithium nickel manganese cobalt composite oxides or lithium cobalt oxides, are used. When using this positive electrode active material, repeated charging and discharging cause cracks to form in the positive electrode active material, reducing its long-term cycle life, increasing its resistance, and resulting in unsatisfactory capacity characteristics, thus requiring improvement. Summary of the Invention

[0004] A positive electrode active material for a rechargeable lithium battery and a rechargeable lithium battery including the positive electrode active material are provided, which achieves high capacity, high initial charge / discharge efficiency, and improved high-temperature cycle life characteristics.

[0005] In an embodiment, the positive electrode active material for a rechargeable lithium battery comprises a lithium-nickel composite oxide, wherein the positive electrode active material is in the form of secondary particles, in which a plurality of primary particles are aggregated and at least a portion of the primary particles are arranged radially. The secondary particles include an inner portion and an outer portion. The inner portion of the secondary particle is a region surrounded by a point located at 50 ± 5% of the total distance from the center of the secondary particle to the surface of the secondary particle, and is a region in which primary particles and pores are irregularly arranged. The outer portion of the secondary particle is a region surrounding the inner portion, wherein at least a portion of the primary particles are arranged radially in the outer portion. In the outer portion of the secondary particle, the number of primary particles with an aspect ratio greater than or equal to about 4 is greater than or equal to about 18%.

[0006] In another embodiment, a method for preparing a positive electrode active material for a rechargeable lithium battery includes heat-treating a mixture of a positive electrode active material precursor comprising a nickel-based composite hydroxide and a lithium raw material, wherein the heat treatment includes a heating process and a holding process, and the heating time is longer than the holding time.

[0007] In another embodiment, the rechargeable lithium battery includes a positive electrode, a negative electrode, and an electrolyte, comprising the aforementioned positive electrode active material.

[0008] The positive electrode active material according to the embodiments and the rechargeable lithium battery including the same achieve high capacity while having high initial charge / discharge efficiency and excellent room temperature and high temperature cycle life characteristics. Attached Figure Description

[0009] Figure 1 A schematic diagram illustrating the shape of the plate-like primary particles.

[0010] Figure 2 This is a view used to explain the radial definition in secondary particles.

[0011] Figure 3 This is a view used to explain the cross-section of the secondary particles and the aspect ratio of the primary particles according to the embodiment.

[0012] Figure 4 A schematic diagram illustrating a rechargeable lithium battery according to an embodiment.

[0013] Figure 5 A scanning electron microscope (SEM) image of the cross-section of the positive electrode active material prepared in Comparative Example 1.

[0014] Figure 6 A scanning electron microscope (SEM) image of the cross-section of the positive electrode active material prepared in Comparative Example 2.

[0015] Figure 7 The image shows the outline of the primary particles in a cross-section of the positive electrode active material prepared in Comparative Example 2, and is a view in which the outer and inner portions are separated.

[0016] Figure 8 This is a scanning electron microscope (SEM) image of the cross-section of the positive electrode active material prepared in Example 1.

[0017] Figure 9 The image shows a contoured view of the primary particles in a cross-section of the positive electrode active material prepared in Example 1, and also shows a view in which the outer and inner portions are separated.

[0018] Figure 10 This is a scanning electron microscope (SEM) image of the cross-section of the positive electrode active material prepared in Example 2.

[0019] Figure 11 The image shows a contoured view of the primary particles in a cross-section of the positive electrode active material prepared in Example 2, and also shows a view in which the outer and inner portions are separated.

[0020] Figure 12Curves showing the aspect ratio distribution of primary particles in the inner portion of the cross-section of the secondary particles of the positive electrode active material prepared in Comparative Example 2, Example 1, and Example 2.

[0021] Figure 13 Curves showing the aspect ratio distribution of primary particles in the outer portion of the cross-section of the secondary particles of the positive electrode active material prepared in Comparative Example 2, Example 1, and Example 2.

[0022] Figure 14 To show the passage Figure 12 The curve analysis of the aspect ratio distribution of primary particles in the internal part of secondary particles is based on the number ratio of aspect ratio ranges.

[0023] Figure 15 To show the passage Figure 13 The aspect ratio distribution curve of the primary particles in the outer part of the secondary particles is analyzed based on the number ratio of the aspect ratio range.

[0024] Figure 16 Curves showing the cross-sectional area distribution of the primary particles in the cross-section of the secondary particles of the positive electrode active material prepared in Comparative Example 1, Example 1, and Example 2.

[0025] Figure 17 To show the passage Figure 16 The area distribution curve of the cross-section of the primary particles is analyzed based on the ratio of the area distribution of the cross-section of the primary particles.

[0026] Figure 18 The graph shows the initial charge capacity, initial discharge capacity, and initial charge / discharge efficiency of the battery cells manufactured in Comparative Example 1, Comparative Example 2, Example 1, and Example 2.

[0027] Figure 19 The graph shows the high-temperature cycle life characteristics, initial discharge capacity, discharge capacity at 50th cycle, and capacity retention rate at 50th cycle of the battery cells manufactured in Comparative Example 1, Comparative Example 2, Example 1, and Example 2. The capacity retention rate at 50th cycle is the ratio of the discharge capacity at 50th cycle to the initial discharge capacity.

[0028] <Explanation of Figure Markers>

[0029] 100: Rechargeable lithium battery; 112: Negative electrode

[0030] 113: Diaphragm; 114: Positive electrode

[0031] 120: Battery casing; 140: Sealing component Detailed Implementation

[0032] Specific implementations will be described in detail below so that those skilled in the art can readily implement them. However, this disclosure may be embodied in many different forms and is not to be construed as limited to the exemplary implementations set forth herein.

[0033] The terminology used herein is for descriptive purposes only and is not intended to limit the invention. Unless the context clearly indicates otherwise, singular expressions also include plural expressions.

[0034] As used herein, "any combination thereof" means mixtures of components, laminates, composites, copolymers, alloys, blends, and reaction products, etc.

[0035] Here it should be understood that terms such as “comprises,” “includes,” or “have” are intended to indicate the presence of specific features, quantities, steps, elements, or any combination thereof, but do not preclude the possibility of the presence or addition of one or more other features, quantities, steps, elements, or any combination thereof.

[0036] In the accompanying drawings, for clarity, the thicknesses of layers, films, panels, areas, etc., are enlarged, and throughout the specification, the same reference numerals denote the same elements. It will be understood that when an element, such as a layer, film, area, or substrate, is referred to as being "on" another element, it may be directly on the other element, or an intervening element may be present. In contrast, when an element is referred to as being "directly on" another element, no intervening element is present.

[0037] In addition, in this paper, “layer” includes not only the shape formed on the entire surface when viewed from a plan view, but also the shape formed on a portion of the surface.

[0038] Additionally, the average particle size and average dimensions can be measured using methods well known to those skilled in the art, for example, by a particle size analyzer, or by transmission electron microscopy or scanning electron microscopy images. Alternatively, the average particle size value may be obtained by measuring the dimensions using dynamic light scattering methods, performing data analysis, counting the number of particles in each particle size range, and thereby calculating. Unless otherwise defined, the average particle size (D50) may refer to the diameter of the particles that constitute 50% of the cumulative volume in a particle size distribution, such as that measured by a particle size analyzer.

[0039] Here, "or" is not interpreted as exclusive. For example, "A or B" can be interpreted as including A, B, and A+B, etc.

[0040] Positive electrode active material

[0041] In one embodiment, the positive electrode active material for a rechargeable lithium battery comprises a lithium-nickel composite oxide, wherein the positive electrode active material is in the form of secondary particles, in which a plurality of primary particles are aggregated and at least a portion of the primary particles are arranged radially. Each secondary particle includes an inner portion and an outer portion surrounding the inner portion, and the number of primary particles in the outer portion having an aspect ratio greater than or equal to about 4 is greater than or equal to about 18%. Here, the number ratio refers to the ratio of the number of primary particles with an aspect ratio greater than or equal to about 4 in the outer portion of the secondary particles to the total number of primary particles in the outer portion of the secondary particles.

[0042] The inner portion of a secondary particle is the area in which primary particles and pores are irregularly arranged, and refers to the area surrounded by a point containing 50 ± 5% of the total distance from the center of the secondary particle to its surface. The outer portion of a secondary particle refers to the area in which at least a portion of the primary particles are arranged radially, as the remaining area surrounding the inner portion.

[0043] Here, the total distance from the center of the secondary particle to its surface can be measured using electron microscopy images of the surface or cross-section of the secondary particle, such as scanning electron microscopy. Additionally, a region representing 50 ± 5% of the total distance from the center of the secondary particle to its surface can be considered as a region representing 45% to 55% of the total distance from the center of the secondary particle to its surface, and can be expressed as a region representing approximately 50% of the total distance from the center of the secondary particle to its surface. That is, the ratio of the diameter of the inner portion of the secondary particle to the diameter of the secondary particle itself can be approximately 45% to approximately 55%, approximately 50% to approximately 55%, or approximately 50%. Here, the diameter of the secondary particle and the diameter of its inner portion are measured using electron microscopy images of the cross-section of the secondary particle. For example, the diameter of the secondary particle and the diameter of its inner portion can be measured by cutting the secondary particle with a focused ion beam (FIB) and observing the cross-section with a scanning electron microscope (SEM).

[0044] Secondary particles may include plate-shaped primary particles. Figure 1 This is a schematic diagram illustrating plate-shaped primary particles. (Reference) Figure 1 Primary particles can have a variety of detailed shapes, while also having basic plate structures, such as (A) polygonal nanoplate shapes, such as hexagons, (B) nanodisc shapes, and (C) cuboid shapes.

[0045] exist Figure 1In this context, "a" refers to the length of the major axis of the primary particle, "b" refers to the length of the minor axis of the primary particle, and "t" refers to the thickness of the primary particle. Here, the length of the major axis, 'a', refers to the maximum length with respect to the widest surface of the primary particle. The thickness, 't', can be the maximum length of the surface approximately perpendicular to the widest surface of the primary particle. The direction containing the lengths of the major axis, 'a', and the minor axis, 'b', is defined as a planar direction, and the direction defining the thickness, 't', is defined as the thickness direction.

[0046] The thickness t of the primary particle can be less than the length a of the major axis and the length b of the minor axis in the planar direction. In the planar direction, the length a of the major axis can be longer than or equal to the length b of the minor axis.

[0047] In the positive electrode active material, at least a portion of the primary particles may have a radial arrangement structure, and for example, the long axis of the primary particles may be arranged in the radial direction. Figure 2 This is a view used to explain the radially defined arrangement of secondary particles according to an embodiment. In the embodiment, a radial arrangement means, as... Figure 2 As shown, the thickness t of the primary particle is perpendicular to the direction R from the center of the secondary particle to the surface of the secondary particle, or forms an angle of approximately ±5° with the direction (R) from the center of the secondary particle to the surface of the secondary particle.

[0048] Thus, when at least a portion of the primary particles are arranged radially, lithium diffusion is improved due to the numerous exposed crystal planes on the surface that transport lithium to the outside, as well as the exposed pores that serve as lithium diffusion channels, ensuring high initial charge / discharge efficiency and high capacity. Furthermore, the pores exposed on the surface of the secondary particles point towards the center of the secondary particles, which further promotes lithium diffusion.

[0049] Due to the radially arranged primary particles, uniform shrinkage and expansion of the positive electrode active material are possible during lithium insertion / extraction and / or deintercalation. Furthermore, during lithium insertion / extraction, more pores exist in the (001) direction, which is the direction of particle expansion, allowing these pores to act as a buffer. Consequently, the probability of cracking during the shrinkage and expansion of the positive electrode active material is reduced, and the internal pores further mitigate volume changes, thereby reducing crack formation between primary particles during charging and discharging. Consequently, the cycle life characteristics of the rechargeable lithium battery can be improved, and the increase in resistance can be reduced.

[0050] Secondary particles comprise an internal portion and an external portion surrounding the internal portion. The secondary particles of the positive electrode active material may include, for example, an internal portion having an irregular porous structure and an external portion having at least a portion of primary particles radially arranged, i.e., a radially arranged structure. The irregular porous structure is a structure having primary particles and pores, wherein the size, shape, and position of the primary particles are irregular. Unlike the external portion, the primary particles may be arranged irregularly in the internal portion.

[0051] The positive electrode active material with this structure has a porous structure in its internal portion, which reduces the diffusion distance of lithium ions to the internal portion, and the pores can mitigate the volume changes between primary particles that occur during charging and discharging. Furthermore, in the positive electrode active material, the primary particles in the external portion are arranged radially, allowing lithium ions to easily embed into the surface and minimizing stress caused by volume changes during charging and discharging. This positive electrode active material can reduce the resistance of rechargeable lithium batteries and improve their initial charge / discharge efficiency and cycle life characteristics.

[0052] In the secondary particles of the positive electrode active material, the internal portion may include pores with a larger size than those in the external portion. For example, the pores in the internal portion may have a size of about 150 nm to about 1 μm, while the pores in the external portion may have a size smaller than about 150 nm. Here, lithium ions can be easily intercalated in the external portion, while the lithium diffusion distance can be shortened in the internal portion, and the effect of mitigating the volume change of the positive electrode active material during charging and discharging can be reduced. Here, when the pore is spherical or circular, the pore may have a size as its diameter, and when the pore is elliptical, etc., the pore may have a size as its length as its major axis, wherein this size is measured using an electron microscope such as SEM.

[0053] Additionally, the secondary particles of the positive electrode active material may have openings on their surface. These openings may be pores with partially open walls, and they may connect to the outside and serve as channels for material to enter and exit. These openings may have a size less than about 150 nm, for example, from about 10 nm to about 148 nm. Because the primary particles in the outer portion of the secondary particles are arranged radially, the openings on the surface may be in the form of extending from the surface of the secondary particles towards the center. The openings may be formed to a depth less than or equal to about 150 nm from the surface of the secondary particles, for example, from about 0.1 nm to about 100 nm, or for example, from about 1 nm to about 50 nm. Here, the size and depth of the openings can be measured using the BJH (Barrett, Joyner, and Halenda) method, which is a method derived from the content of adsorbed or desorbed nitrogen.

[0054] Closed pores can exist in the internal portion of secondary particles, and closed pores and / or open pores can exist in the external portion. Closed pores can exclude or almost exclude electrolytes, while open pores can contain electrolytes. Closed pores can be referred to as independent pores that are not connected to other pores because all walls of a closed pore are formed in a closed-pore structure.

[0055] In the positive electrode active material according to the embodiment, the proportion of primary particles with an aspect ratio greater than or equal to about 4 in the outer portion of the secondary particles is greater than or equal to about 18%. Since this positive electrode active material is more conducive to lithium-ion movement, stress caused by contraction and expansion is minimized, and in particular, structural stability at high temperatures is improved, while simultaneously achieving high capacity. Accordingly, the capacity of rechargeable lithium batteries can be increased, while initial charge / discharge efficiency and high-temperature cycle life characteristics can be improved.

[0056] In this paper, the aspect ratio of primary particles refers to the aspect ratio of the cross-section of the primary particles as observed in the cross-section of secondary particles, which can be measured in electron microscopy images of the cross-section of secondary particles of the positive electrode active material using an image analysis program. For example, secondary particles are cut with a focused ion beam (FIB), and images of the cross-section are taken using a scanning electron microscope (SEM). The SEM images of the primary particles are then contour-processed using an image analysis program (Image J program) to measure the aspect ratio of the contour-processed primary particles.

[0057] The aspect ratio of primary particles can be measured using various image processing programs, such as ImageJ. ImageJ is software developed by the National Institutes of Health and others and can be downloaded from https: / / imagej.net / ImageJ. For a detailed description, see https: / / en.Wikipedia.org / wiki / ImageJ, etc.

[0058] Specifically, a method for obtaining the proportion of primary particles with an aspect ratio greater than or equal to about 4 in the outer portion of secondary particles can be, for example, as follows: In an electron microscopy image of a cross-section of a secondary particle cut with FIB, the primary particles are contoured using the ImageJ program. In the contoured image, the inner and outer portions of the secondary particles are distinguished. Here, the inner portion is defined as the area surrounded by a point approximately 50% of the total distance from the center of the secondary particle to its surface, and the remaining area outside the inner portion is defined as the outer portion, wherein primary particles spanning 50% of the total distance, i.e., primary particles at the boundary, are defined as included in the inner portion. Subsequently, the aspect ratio of all primary particles contoured in each inner and outer portion is measured using the ImageJ program to analyze the aspect ratio distribution. Here, the proportion of primary particles with an aspect ratio greater than or equal to about 4 in the outer portion of secondary particles can be derived.

[0059] Figure 3 This is a view used to explain the cross-section of the secondary particles and the aspect ratio of the primary particles according to the embodiment. Figure 3 This image is obtained by contour processing of the primary particles using the ImageJ program in an SEM image of a cross-section of the positive electrode active material according to the embodiment, cut using FIB. Black portions represent the internal parts of the secondary particles, and white portions represent the external parts. In this document, a primary particle is magnified and provided... Figure 3 At the top. In the selected primary particle, draw two parallel lines to form a sandwich shape, and the longest length between these two parallel lines (major axis; horizontal axis; width; long side) is called "x", while the vertical length (minor axis; vertical axis; height; short side) is called "y". In this paper, the aspect ratio of the primary particle refers to the ratio of x to y, that is, x / y.

[0060] The proportion of primary particles with an aspect ratio greater than or equal to about 4 in the outer portion of the secondary particles can be, for example, about 18% to about 45%, about 18% to about 40%, about 18% to about 35%, or about 18% to about 30%. When the proportion of primary particles with an aspect ratio greater than or equal to about 4 meets this range, the positive electrode active material can exhibit high initial charge / discharge efficiency and excellent high-temperature cycle life characteristics, while achieving high capacity.

[0061] Furthermore, the proportion of primary particles with an aspect ratio of less than or equal to about 2.5 in the outer portion of the secondary particles may be less than or equal to about 54%, for example, about 20% to about 54%, about 30% to about 54%, or about 35% to about 54%.

[0062] The number ratio of primary particles with an aspect ratio greater than about 2.5 and less than about 4 may be, for example, about 1% to about 62%, about 6% to about 62%, about 11% to about 62%, about 16% to about 62%, about 1% to about 52%, or about 1% to about 47%.

[0063] When the aspect ratio of the primary particles in the outer portion of the secondary particles exhibits this distribution, the positive electrode active material can exhibit high initial charge / discharge efficiency and excellent high-temperature cycle life, while achieving high capacity.

[0064] The internal and external portions of secondary particles can exhibit different aspect ratios of the primary particles. For example, the proportion of primary particles with an aspect ratio greater than or equal to about 4 in the external portion of secondary particles can be three times or greater than the proportion of primary particles with an aspect ratio greater than or equal to about 4 in the internal portion of secondary particles.

[0065] Additionally, the proportion of primary particles with an aspect ratio greater than or equal to about 4 in the internal portion of the secondary particles may be less than about 18%, for example, less than or equal to about 15%, about 5% to about 15%, or about 5% to about 10%.

[0066] Within the secondary particles, the proportion of primary particles with an aspect ratio less than or equal to about 2.5 may be less than or equal to about 71%, for example, about 40% to about 71%, about 50% to about 71%, or about 60% to about 71%.

[0067] When the internal and external portions of the secondary particles exhibit the same aspect ratio distribution as the primary particles, the positive electrode active material can exhibit high initial charge / discharge efficiency and excellent high-temperature cycle life, and achieve high capacity.

[0068] On the other hand, embodiments provide a positive electrode active material for a rechargeable lithium battery comprising a lithium-nickel composite oxide, wherein multiple primary particles aggregate into secondary particles, and at least a portion of the primary particles are radially arranged, wherein the cross-sectional area of ​​the secondary particles is less than about 0.1 μm. 2 The proportion of primary particles is approximately 70% or greater.

[0069] This positive electrode active material readily ensures lithium transfer pathways between primary particles, and the pores between the primary particles mitigate volume changes in the positive electrode active material during charging and discharging, thus minimizing stress caused by volume changes. Consequently, the resistance of the rechargeable lithium battery can be reduced, and capacity and cycle life characteristics can be improved.

[0070] In this paper, the cross-sectional area of ​​primary particles can be measured from electron microscopy images of the cross-section of secondary particles using an image processing program. For example, it can be measured by contouring the primary particles on the cross-section of the secondary particles using the ImageJ program in SEM images of positive electrode active material cut with focused ion beam (FIB). Specifically, the SEM images of the FIB cross-section of the secondary particles are input into a computer to contour the primary particles using the ImageJ program, and the area of ​​all contoured primary particles is measured to analyze the area distribution, from which it can be deduced that the cross-sectional area is less than about 0.1 μm. 2 The ratio of the number of primary particles, etc.

[0071] In the cross-section of the secondary particles, the cross-sectional area is less than 0.1 μm. 2 The proportion of primary particles can be, for example, about 70% to about 90%, about 70% to about 85%, or about 70% to about 80%.

[0072] Furthermore, the cross-sectional area of ​​the secondary particles is greater than approximately 0.3 μm. 2 The number of primary particles may be less than or equal to about 5%, for example, about 0% to about 5%, about 0.1% to about 5%, or about 1% to about 5%.

[0073] The cross-sectional area of ​​the secondary particles is approximately 0.1 μm. 2 To approximately 0.3μm 2 The proportion of primary particles can be from about 5% to about 30%, from about 10% to about 29.9%, or from about 15% to about 29%.

[0074] When the cross-sectional area of ​​the primary particles has this distribution, the positive electrode active material can exhibit high initial charge / discharge efficiency and excellent high-temperature cycle life, while achieving high capacity.

[0075] The average particle size of the secondary particles of the positive electrode active material can be from about 8 μm to about 20 μm, for example, from about 8 μm to about 18 μm or from about 10 μm to about 15 μm. Here, the positive electrode active material can achieve high capacity and exhibit high initial charge / discharge efficiency and cycle life characteristics.

[0076] Here, the average particle size of the secondary particles can be measured by laser diffraction, by mixing the positive electrode active material with a dispersant and dispersing it in water, and for example, by using a Beckman Coulter LS 13 320 particle size analyzer. The particle size distribution is obtained by the particle size analyzer, and the D50, which is the particle size at a point where the cumulative volume is 50% of the total volume, can be considered as the average particle size.

[0077] On the other hand, the cross-sectional data of the primary particles can be analyzed by selecting secondary particles as examples. Particles with a size similar to the D50 measured by laser diffraction are selected from electron microscope images of the positive electrode active material. The selected particles are cut using FIB and the cross-section is photographed using an electron microscope. The primary particles are then contoured using an image processing program such as ImageJ. Here, the area surrounded by the point where 50% of the total distance from the center of the secondary particle to its surface is located is defined as the inner portion, and the area outside the inner portion is defined as the outer portion. The primary particles at the 50% length boundary are defined as included in the inner portion, and thus the aspect ratio of the primary particles in the inner and outer portions can be analyzed separately. Additionally, the cross-sectional area of ​​the primary particles in the entire cross-section of the secondary particles can be analyzed.

[0078] Lithium-nickel composite oxides can be represented by chemical formula 1.

[0079] [Chemical Formula 1]

[0080] Li a1 Ni x1 M 1 y1 M 2 1-x1-y1 O 2-z X z ,

[0081] In chemical formula 1, 0.9 ≤ a1 ≤ 1.8, 0.3 ≤ x1 ≤ 1, 0 ≤ y1 ≤ 0.7 and 0 ≤ z ≤ 0.1, M 1 and M 2 Each element is independently selected from at least one element chosen from Al, B, Ba, Ca, Ce, Co, Cr, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, and Zr, and X is selected from at least one element chosen from F, P, and S.

[0082] In chemical formula 1, 0.4≤x1≤1 and 0≤y1≤0.6, 0.5≤x1≤1 and 0≤y1≤0.5, 0.6≤x1≤1 and 0≤y1≤0.4, or 0.7≤x1≤1 and 0≤y1≤0.3, 0.8≤x1≤1 and 0≤y1≤0.2, or 0.9≤x1≤1 and 0≤y1≤0.1.

[0083] Lithium-nickel composite oxides can, for example, be represented by chemical formula 2.

[0084] [Chemical Formula 2]

[0085] Li a2 Ni x2 Co y2 M3 1-x2-y2 O 2-z X z ,

[0086] In Chemical Formula 2, 0.9≤a2≤1.8, 0.3≤x2<1, 0<y2≤0.7 and 0≤z≤0.1, M 3 is at least one element selected from Al, B, Ba, Ca, Ce, Cr, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W and Zr, and X is at least one element selected from F, P and S.

[0087] In Chemical Formula 2, 0.3≤x2≤0.99 and 0.01≤y2≤0.7, 0.4≤x2≤0.99 and 0.01≤y2≤0.6, 0.5≤x2≤0.99 and 0.01≤y2≤0.5, or 0.6≤x2≤0.99 and 0.01≤y2≤0.4, 0.7≤x2≤0.99 and 0.01≤y2≤0.3, 0.8≤x2≤0.99 and 0.01≤y2≤0.2, or 0.9≤x2≤0.99 and 0.01≤y2≤0.1.

[0088] The lithium-nickel-based composite oxide may be represented by, for example, Chemical Formula 3.

[0089] [Chemical Formula 3]

[0090] Li a3 Ni x3 Co y3 M 4 z3 M 5 1-x3-y3-z3 O 2-z X z ,

[0091] In Chemical Formula 3, 0.9≤a3≤1.8, 0.3≤x3≤0.98, 0.01≤y3≤0.69, 0.01≤z3≤0.69, and 0≤z≤0.1, M 4 is at least one element selected from Al and Mn, M 5 is at least one element selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sr, Ti, V, W and Zr, and X is at least one element selected from F, P and S.

[0092] In chemical formula 3, 0.4≤x3≤0.98, 0.01≤y3≤0.59 and 0.01≤z3≤0.59, 0.5≤x3≤0.98, 0.01≤y3≤0.49 and 0.01≤z3≤0.49, 0.6≤x3≤0.98, 0.01≤y3≤0.39 and 0.01≤z3≤0.39, 0.7≤x3≤0.98, 0.01≤y3≤0.29 and 0.01≤z3≤0.29, 0.8≤x3≤0.98, 0.01≤y3≤0.19 and 0.01≤z3≤0.19, or 0.9≤x3≤0.98, 0.01≤y3≤0.09 and 0.01≤z3≤0.09.

[0093] Methods for preparing positive electrode active materials

[0094] In one embodiment, a method for preparing a positive electrode active material for a rechargeable lithium battery includes mixing a positive electrode active material precursor comprising a nickel-based complex hydroxide with a lithium raw material, and then heat-treating the resulting product.

[0095] The precursor for the positive electrode active material can be prepared by a co-precipitation method. In other words, a nickel raw material is mixed with an optional metal raw material other than nickel to prepare a composite metal raw material, and then a complexing agent and a pH control agent are added to control the pH of the mixture and a co-precipitation reaction is carried out to prepare a nickel-based composite hydroxide with the desired composition.

[0096] Complexing agents are used to control the reaction rate of precipitate formation in coprecipitation reactions, and can be, for example, ammonium hydroxide (NH4OH) or citric acid.

[0097] pH control reagents can be, for example, sodium hydroxide (NaOH), sodium carbonate (Na₂CO₃), or sodium oxalate (Na₂C₂O₄). The pH of the mixture can be adjusted to, for example, a range of about 10 to about 13.

[0098] The co-precipitation reaction can be carried out in several steps, such as two, three, or four steps. In each step, the concentration of the complexing agent, the input rate of the composite metal raw material, the pH range, the reaction temperature, the reaction time, and the stirring power can be adjusted differently. Through these adjustments, a secondary particulate positive electrode active material precursor is prepared, wherein at least a portion of the primary particles are radially arranged, and in addition, secondary particles with different internal and external shapes are prepared.

[0099] In one embodiment, a positive electrode active material precursor comprising a nickel-based composite hydroxide is prepared by forming a core, an intermediate layer, and a shell through respective first, second, and third steps.

[0100] In the first step, a complexing agent and a pH control reagent are placed in a reactor, and a composite metal raw material is added and reacted. The complexing agent can have a concentration of 0.1M to 0.7M, and the input rate of the complexing agent can be in the range of 6mL / min to 12mL / min. The composite metal raw material can have a concentration of 0.1M to 3.5M, and the input rate of the composite metal raw material can be in the range of 50mL / min to 100mL / min.

[0101] In the second step, the composite metal raw material and the complexing agent are added to the material obtained from the reaction in the first step to control the pH of the reaction mixture, and then the second step reaction is carried out. The concentration of the complexing agent can be from 0.3M to 1.0M, and the input rate of the complexing agent can be in the range of 8 ml / min to 15 ml / min. The composite metal raw material can have a concentration from 0.1M to 3.5M, and the input rate of the composite metal raw material can be in the range of 90 ml / min to 120 ml / min.

[0102] In the third step, the input amount and concentration of the composite metal raw material and the complexing agent can be increased to prevent the growth rate of the particles from the reaction product in the second step from decreasing after a predetermined reaction time. The concentration of the complexing agent can be in the range of 0.35M to 1.0M, the input amount of the complexing agent can be in the range of 12ml / min to 20ml / min, the composite metal raw material can have a concentration of 0.1M to 3.5M, and the input amount of the composite metal raw material can be in the range of 120ml / min to 150ml / min.

[0103] In the first, second, and third steps, the pH of the reaction mixture can be adjusted to be in the range of 10 to 12.

[0104] Nickel-based complex hydroxides can, for example, be represented by chemical formula 11.

[0105] [Chemical Formula 11]

[0106] Ni x11 M 11 y11 M 12 1-x11-y11 (OH)2,

[0107] In chemical formula 11, 0.3 ≤ x11 ≤ 1, 0 ≤ y11 ≤ 0.7, and M 11 and M 12 Each element is independently selected from at least one element selected from Al, B, Ba, Ca, Ce, Co, Cr, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, and Zr.

[0108] As a specific example, the nickel-based composite hydroxide may be represented by Chemical Formula 12 or Chemical Formula 13.

[0109] [Chemical Formula 12]

[0110] Ni x12 Co y12 M 13 1-x12-y12 (OH)₂,

[0111] In Chemical Formula 12, 0.3≤x12<1, 0<y12≤0.7, and M 13 is at least one element selected from the group consisting of Al, B, Ba, Ca, Ce, Cr, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, and Zr.

[0112] [Chemical Formula 13]

[0113] Ni x13 Co y13 M 14 z13 M 15 1-x13-y13-z13 (OH)₂,

[0114] In Chemical Formula 13, 0.3≤x13≤0.98, 0.01≤y13≤0.69, 0.01≤z13≤0.69, M 14 is selected from Al, Mn, and any combination thereof, and M 15 is at least one element selected from the group consisting of B, Ba, Ca, Ce, Cr, F, Fe, Mg, Mo, Nb, P, S, Si, Sr, Ti, V, W, and Zr.

[0115] The average particle diameter (D50) of the positive electrode active material precursor may be, for example, about 7 μm to about 25 μm or about 8 μm to about 20 μm. Herein, the particle size of the positive electrode active material precursor may be measured through an electron microscope image such as a scanning electron microscope. The average particle size may be obtained by measuring the sizes of about 50 particles with an electron microscope to obtain a particle size distribution, and the D50 value, which is the particle size at the point where the cumulative volume is about 50 vol%, may be regarded as the average particle diameter.

[0116] The aforementioned positive electrode active material may be obtained by mixing a lithium raw material with the prepared positive electrode active material precursor, and then performing a heat treatment.

[0117] The lithium raw material may be, for example, Li₂CO₃, LiOH, a hydrate thereof, or any combination thereof, and may be mixed at a ratio of about 0.8 mol to about 1.8 mol or about 0.9 mol to about 1.2 mol relative to 1 mol of the nickel-based composite hydroxide.

[0118] Heat treatment may be performed, for example, at about 600°C to about 900°C or about 600°C to about 800°C.

[0119] In this embodiment, the heat treatment may include a heating process and a holding process, wherein the heating time may be longer than the holding time. For example, the heating time may be from about 6 hours to about 16 hours, and the holding time may be from about 1 hour to about 9 hours, wherein the heating time may be longer than the holding time.

[0120] In heat treatment, the heating time can be, for example, about 6 hours to about 15 hours, about 6 hours to about 14 hours, about 6 hours to about 13 hours, or about 7 hours to about 12 hours, and the holding time can be about 2 hours to about 9 hours or about 3 hours to about 8 hours.

[0121] Additionally, the ratio of (heating time):(holding time) can be from about 1.1:1 to about 10:1, for example, from about 1.1:1 to about 8:1, from about 1.1:1 to about 6:1, from about 1.1:1 to about 5:1 or from about 1.1:1 to about 4:1.

[0122] In this way, the heat treatment curve is adjusted to effectively prepare the positive electrode active material, wherein the aspect ratio and / or cross-sectional area of ​​the primary particles in the inner and outer portions of the secondary particles are as designed above.

[0123] positive electrode

[0124] The positive electrode for a rechargeable lithium-ion battery may include a positive electrode current collector and a layer of positive electrode active material on the positive electrode current collector. The positive electrode active material layer may include a positive electrode active material and may further include a binder and / or a conductive material.

[0125] The binder improves the adhesion properties between the positive electrode active material particles and between the positive electrode active material particles and the positive electrode current collector. Examples of binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic styrene-butadiene rubber, epoxy resin, and nylon, but are not limited to these.

[0126] Based on the total weight of the positive electrode active material layer, the binder content in the positive electrode active material layer can be from about 1 wt% to about 5 wt%.

[0127] Conductive materials are included to provide electrode conductivity. Any electrically conductive material can be used as a conductive material unless it causes a chemical change. Examples of conductive materials may include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, and carbon nanotubes; metallic materials including metal powders or fibers of metals such as copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; or mixtures thereof.

[0128] Based on the total weight of the positive electrode active material layer, the content of conductive material in the positive electrode active material layer can be from about 1 wt% to about 5 wt%.

[0129] Aluminum foil can be used as a positive electrode current collector, but this disclosure is not limited thereto.

[0130] negative electrode

[0131] The negative electrode for a rechargeable lithium battery includes a negative electrode current collector and a layer of negative electrode active material on the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material and may further include a binder and / or a conductive material.

[0132] Negative electrode active materials may include materials that can reversibly insert / deintercalate lithium ions, lithium metal, lithium metal alloys, materials that can be doped / dedoped with lithium, or transition metal oxides.

[0133] Materials that can reversibly insert / deintercalate lithium ions can include, for example, crystalline carbon, amorphous carbon, or any combination thereof as carbon-based anode active materials. Crystalline carbon can be shapeless, flake-like, spherical, or fibrous natural or artificial graphite. Amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbonization products, and calcined coke, etc.

[0134] Lithium metal alloys include alloys of lithium with metals selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.

[0135] Materials capable of lithium doping / de-doping can be Si-based or Sn-based anode active materials. Si-based anode active materials can include silicon, silicon-carbon composites, and SiO₂. x(0<x<2), a Si-Q alloy (where Q is an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element other than Si, a Group 15 element, a Group 16 element, a transition metal, a rare earth element, and any combination thereof), and the Sn-based negative electrode active material may include Sn, SnO₂, a Sn-R alloy (where R is an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element other than Sn, a Group 15 element, a Group 16 element, a transition metal, a rare earth element, and any combination thereof). At least one of these materials may be mixed with SiO₂. Elements Q and R may be selected from Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and any combination thereof.

[0136] The silicon-carbon composite material may be, for example, a silicon-carbon composite material, which includes: a core comprising crystalline carbon and silicon particles, and an amorphous carbon coating disposed on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or any combination thereof. The amorphous carbon precursor may be coal-based pitch, mesophase pitch, petroleum-based pitch, coal-based oil, petroleum-based heavy oil, or a polymer resin such as a phenolic resin, a furan resin, or a polyimide resin. In this case, based on the total weight of the silicon-carbon composite material, the content of silicon may be about 10 wt% to about 50 wt%. In addition, based on the total weight of the silicon-carbon composite material, the content of crystalline carbon may be about 10 wt% to about 70 wt%, and based on the total weight of the silicon-carbon composite material, the content of amorphous carbon may be about 20 wt% to about 40 wt%. Further, the thickness of the amorphous carbon coating may be about 5 nm to about 100 nm. The average particle diameter (D50) of the silicon particles may be about 10 nm to about 20 μm. The average particle diameter (D50) of the silicon particles may preferably be about 10 nm to about 200 nm. The silicon particles may exist in an oxidized form, and in this case, the atomic content ratio of Si:O indicating the oxidation degree in the silicon particles may be about 99:1 to about 33:67. The silicon particles may be SiO x particles, and in this case, SiO x the range of x in may be greater than about 0 and less than about 2.

[0137] The Si-based negative electrode active material or the Sn-based negative electrode active material may be mixed with a carbon-based negative electrode active material. When the Si-based negative electrode active material or the Sn-based negative electrode active material is mixed with the carbon-based negative electrode active material for use, the mixing ratio may be a weight ratio of about 1:99 to about 90:10.

[0138] In the negative electrode active material layer, the amount of negative electrode active material included, based on the total weight of the negative electrode active material layer, can be from about 95 wt% to about 99 wt%.

[0139] In an embodiment, the negative electrode active material layer further includes a binder and optionally further includes a conductive material. Based on the total weight of the negative electrode active material layer, the binder content in the negative electrode active material layer can be from about 1 wt% to about 5 wt%. Alternatively, when further including a conductive material, the negative electrode active material layer may include about 90 wt% to about 98 wt% of negative electrode active material, about 1 wt% to about 5 wt% of binder, and about 1 wt% to about 5 wt% of conductive material.

[0140] The binder is used to bond the negative electrode active material particles together effectively, and also to bond the negative electrode active material to the negative electrode current collector. The binder can be a water-insoluble binder, a water-soluble binder, or any combination thereof.

[0141] Examples of water-insoluble adhesives include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, ethylene propylene copolymers, polystyrene, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyimide, or any combination thereof.

[0142] Water-soluble adhesives may include rubber adhesives or polymeric resin adhesives. Rubber adhesives may be selected from styrene-butadiene rubber, acrylic styrene-butadiene rubber, acrylonitrile-butadiene rubber, acrylic rubber, butyl rubber, fluororubber, and any combination thereof. Polymeric resin adhesives may be selected from polyethylene oxide, polyvinylpyrrolidone, polyepoxychloropropane, polyphosphazene, polyacrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and any combination thereof.

[0143] When a water-soluble binder is used as a negative electrode binder, it may further include a cellulose-based compound capable of imparting viscosity as a thickener. As a cellulose-based compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, and their alkali metal salts may be mixed and used. As an alkali metal, Na, K, or Li may be used. Based on 100 parts by weight of the negative electrode active material, the amount of thickener may be from about 0.1 parts by weight to about 3 parts by weight.

[0144] Conductive materials are included to provide electrode conductivity. Any electrically conductive material can be used as a conductive material unless it causes a chemical change. Examples of conductive materials include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, and carbon nanotubes; metallic materials including metal powders or fibers of copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; or mixtures thereof.

[0145] The negative electrode current collector may include one selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, polymer substrate coated with conductive metal, and any combination thereof.

[0146] Rechargeable lithium battery

[0147] Another embodiment provides a rechargeable lithium battery comprising a positive electrode, a negative electrode, and an electrolyte.

[0148] Rechargeable lithium batteries may include, for example, a positive electrode, a negative electrode, a separator between the positive and negative electrodes, and an electrolyte, wherein the electrolyte may be in the form of a liquid or a gel polymer. As another example, a rechargeable lithium battery may be an all-solid-state battery comprising a positive electrode, a negative electrode, and a solid electrolyte, or a semi-solid-state battery comprising a positive electrode, a negative electrode, and a semi-solid electrolyte. Semi-solid may refer to a state comprising both solid and liquid components, or a state comprising mostly solid components but including a portion of liquid components. All-solid-state and semi-solid-state batteries may not include a separator. The positive electrode active material according to the embodiments achieves very high initial charge / discharge efficiency and high-temperature cycle life, while also achieving high capacity due to its shape, thus making it suitable for use in batteries of the aforementioned types and exhibiting excellent performance in each battery.

[0149] As an example, a rechargeable lithium battery including a separator and a liquid electrolyte is described. Figure 4 A schematic diagram illustrating a rechargeable lithium battery according to an embodiment. (Reference) Figure 4 According to an embodiment, a rechargeable lithium battery 100 includes: a battery cell including a positive electrode 114, a negative electrode 112 facing the positive electrode 114, a separator 113 between the positive electrode 114 and the negative electrode 112, an electrolyte for a rechargeable lithium battery impregnating the positive electrode 114, the negative electrode 112 and the separator 113; a battery casing 120 containing the battery cell; and a sealing member 140 sealing the battery casing 120.

[0150] Electrolytes include non-aqueous organic solvents and lithium salts.

[0151] Non-aqueous organic solvents are used as media for transporting ions involved in the electrochemical reactions of a battery. Non-aqueous organic solvents can include carbonate solvents, ester solvents, ether solvents, ketone solvents, alcohol solvents, or aprotic solvents. Carbonate solvents can include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene glycol carbonate (EC), propylene glycol carbonate (PC), and butylene glycol carbonate (BC), etc. Ester solvents can include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, decanolactone, valerate, mevalonolactone, and caprolactone, etc. Ether solvents can include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, and tetrahydrofuran, etc., and ketone solvents can include cyclohexanone, etc. In addition, alcohol solvents may include ethanol and isopropanol, and aprotic solvents may include nitriles such as R-CN (where R is a C2 to C20 straight-chain, branched or cyclic hydrocarbon group, and may include double bonds, aromatic rings or ether bonds), amides such as dimethylformamide, dioxolane such as 1,3-dioxolane, and sulfolane.

[0152] It can be used alone or in mixtures with non-aqueous organic solvents. When using non-aqueous organic solvents in mixtures, the mixture ratio can be controlled according to the desired battery performance.

[0153] Alternatively, carbonate solvents may include mixtures of cyclic and chain carbonates. In this case, the electrolyte exhibits superior performance when the cyclic and chain carbonates are mixed in a volume ratio of about 1:1 to about 1:9.

[0154] The non-aqueous organic solvent may further include aromatic hydrocarbon organic solvents among carbonate solvents. In this case, the carbonate solvent and the aromatic hydrocarbon organic solvent may be mixed in a volume ratio of about 1:1 to about 30:1.

[0155] As an aromatic hydrocarbon organic solvent, aromatic hydrocarbon compounds represented by chemical formula I can be used.

[0156] [Chemical Formula I]

[0157]

[0158] In chemical formula I, R 4 To R 9 The same or different and selected from hydrogen, halogen, C1 to C10 alkyl, C1 to C10 haloalkyl and any combination thereof.

[0159] Specific examples of aromatic hydrocarbon organic solvents may be selected from benzene, fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, chlorobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, iodobenzene, 1,2-diiodobenzene, 1,3-diiodobenzene, 1,4-diiodobenzene, 1,2,3-triiodobenzene, 1,2,4-triiodobenzene, toluene, and fluorotoluene. 2,3-Difluorotoluene, 2,4-Difluorotoluene, 2,5-Difluorotoluene, 2,3,4-Trifluorotoluene, 2,3,5-Trifluorotoluene, Chlorotoluene, 2,3-Dichlorotoluene, 2,4-Dichlorotoluene, 2,5-Dichlorotoluene, 2,3,4-Trichlorotoluene, 2,3,5-Trichlorotoluene, Iodotoluene, 2,3-Diiodotoluene, 2,4-Diiodotoluene, 2,5-Diiodotoluene, 2,3,4-Triiodotoluene, 2,3,5-Triiodotoluene, Xylene, and any combination thereof.

[0160] The electrolyte may further include vinylene carbonate or ethylene glycol carbonate compounds of formula II in order to improve the cycle life of the battery.

[0161] [Chemical Formula II]

[0162]

[0163] In chemical formula II, R 10 and R 11 The same or different, and selected from hydrogen, halogen, cyano, nitro and fluorinated C1 to C5 alkyl groups, under the condition that R 10 and R 11 At least one of them is selected from halogen, cyano, nitro and fluorinated C1 to C5 alkyl groups, but R 10 and R 11 Not all of them are hydrogen.

[0164] Examples of ethylene glycol carbonate compounds may be difluoroethylene glycol carbonate, chloroethylene glycol carbonate, dichloroethylene glycol carbonate, bromoethylene glycol carbonate, dibromoethylene glycol carbonate, nitroethylene glycol carbonate, cyanoethylene glycol carbonate, or fluoroethylene glycol carbonate. The amount of additives used to improve cycle life may be used within appropriate limits.

[0165] Lithium salts dissolved in non-aqueous organic solvents supply lithium ions to the battery, ensuring basic operation of the rechargeable lithium battery and improving lithium ion transport between the positive and negative electrodes.

[0166] Examples of lithium salts include at least one supported salt selected from the following: LiPF6, LiBF4, LiSbF6, LiAsF6, LiN(SO2C2F5)2, Li(CF3SO2)2N, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide: LiFSI), LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2 (where x and y are natural numbers, for example, integers ranging from 1 to 20), lithium difluoro(bis(oxalate)phosphate), LiCl, LiI, LiB(C2O4)2 (lithium bis(oxalate)borate, LiBOB) and lithium difluoro(oxalate)borate (LiDFOB).

[0167] Lithium salts can be used at concentrations ranging from about 0.1 M to about 2.0 M. When lithium salts are included in the above concentration range, the electrolyte exhibits excellent performance and lithium-ion mobility due to optimal electrolyte conductivity and viscosity.

[0168] The separator 113 separates the positive electrode 114 and the negative electrode 112 and provides a transport channel for lithium ions. It can be any commonly used separator in lithium-ion batteries. In other words, it can have low resistance to ion transport and excellent impregnation properties with the electrolyte. For example, the separator 113 can comprise glass fiber, polyester, polyethylene, polypropylene, polytetrafluoroethylene, or any combination thereof, and can be in the form of non-woven or woven fabrics. For example, in lithium-ion batteries, polyolefin polymers, such as polyethylene and polypropylene, can be primarily used as the material for the separator 113. To ensure heat resistance or mechanical strength, coated separators comprising ceramic components or polymer materials can be used. Optionally, it can have a single-layer or multi-layer structure.

[0169] Based on the type of separator and electrolyte used in rechargeable lithium batteries, they can be classified into lithium-ion batteries, lithium-ion polymer batteries, and lithium polymer batteries. Rechargeable lithium batteries can have various shapes and sizes, including cylindrical, prismatic, coin-shaped, or pouch-shaped batteries, and can be thin-film batteries or quite large in size. The structures and manufacturing methods for rechargeable lithium secondary batteries disclosed herein are well known in the art.

[0170] The rechargeable lithium battery according to the embodiments can be used in electric vehicles (EVs), hybrid electric vehicles such as plug-in hybrid electric vehicles (PHEVs), and portable electronic devices because it achieves high capacity and has excellent storage stability, cycle life characteristics, and high rate capability at high temperatures.

[0171] The following describes embodiments and comparative examples of the present invention. However, it should be understood that these embodiments are for illustrative purposes and are not intended to limit the invention.

[0172] Comparative Example 1

[0173] 1. Preparation of positive electrode active material precursor

[0174] Nickel sulfate, cobalt sulfate, and aluminum nitrate were dissolved in distilled water at a molar ratio of 94.5:4:1.5 to prepare a mixed solution of composite metal raw materials. A dilute ammonia solution (NH4OH) and sodium hydroxide (NaOH) were prepared as a precipitant to form a composite compound.

[0175] After adding a dilute ammonia solution to a continuous reactor, a mixed solution of composite metal raw materials is continuously added, and sodium hydroxide is added to maintain the pH within the reactor. The reaction proceeds slowly for approximately 80 hours, and when the reaction stabilizes, the overflowing product is collected and dried.

[0176] Accordingly, nickel-based composite hydroxides (Ni) in the form of secondary particles were prepared. 0.945 Co 0.04 Al 0.015 (OH)2), in which the primary particles are not radially arranged in the secondary particles.

[0177] 2. Preparation of positive electrode active material

[0178] In an oxygen atmosphere, 100 moles of LiOH were mixed with 100 moles of the obtained nickel-based composite hydroxide, and the temperature was raised to 730°C over 5 hours, followed by heat treatment for 7 hours to prepare a non-radial nickel-based composite oxide (LiNi). 0.945 Co 0.04 Al 0.015 O2), which is the positive electrode active material.

[0179] 3. Manufacturing of the positive electrode

[0180] 96 wt% of the obtained positive electrode active material, 2 wt% of polyvinylidene fluoride, 2 wt% of carbon nanotubes, and N-methylpyrrolidone as a solvent were mixed in a mixer to prepare a slurry for the positive electrode active material layer. The slurry for the positive electrode active material layer was coated onto aluminum foil to form an electrode plate, and then dried at 135°C for at least 3 hours, rolled, and vacuum dried to manufacture the positive electrode.

[0181] 4. Manufacturing of individual battery cells

[0182] The positive electrode and lithium metal counter electrode are used to manufacture the coin half-cell cell. A separator formed of a porous polyethylene membrane (thickness: approximately 16 μm) is inserted between the positive electrode and the lithium metal counter electrode, and an electrolyte is injected into it. The electrolyte is prepared by mixing ethylene glycol carbonate (EC) and ethyl methyl carbonate (EMC) in a 3:5 volume ratio and dissolving 1.1 M LiPF6 in the mixed solvent.

[0183] Comparative Example 2

[0184] 1. Preparation of positive electrode active material precursor

[0185] In the following coprecipitation method, nickel sulfate, cobalt sulfate, and aluminum nitrate are used as composite metal raw materials.

[0186] [First step: 2.5kW / m] 3 [NH4OH 0.40M, pH 10.5 to 11.5 and reaction time 6 hours]

[0187] First, 0.40M ammonia solution is added to the reactor. (At 2.5kW / m³) 3 Under the stirring power, the composite metal raw material and complexing agent (NH4OH) were added at 85 ml / min and 10 ml / min respectively at 50℃, and the reaction started simultaneously.

[0188] The reaction proceeded for 6 hours while NaOH was added to maintain the pH in the range of 10.5 to 11.5. As a result of the reaction, the average size of the obtained nuclei was confirmed to be in the range of approximately 6.5 μm to 7.5 μm, and the second step was carried out as follows.

[0189] [Second step: 2.0kW / m] 3 [NH4OH 0.45M, pH 10.5 to 11.5 and reaction time 18 hours]

[0190] The composite metal raw material and complexing agent were added at rates of 107 ml / min and 15 ml / min, respectively, while maintaining the reaction temperature at 50°C and keeping the complexing agent concentration at 0.45 M. NaOH was added to maintain the pH between 10.5 and 11.5, and the reaction proceeded for 18 hours. At this point, the stirring power was reduced to 2.0 kW / m³. 3 (This is lower than the stirring power in the first step), and the reaction continues. By carrying out this reaction, the average size of the product particles containing the core and intermediate layer was confirmed to be 11.5 μm to 12 μm, and the third step is carried out as follows.

[0191] [Third step: 1.0kW / m] 3[NH4OH 0.45M, pH 10.5-11.5 and reaction time 10 hours]

[0192] While maintaining the reaction temperature at 50°C, the composite metal raw material and complexing agent were added at rates of 142 ml / min and 19 ml / min, respectively, to ensure that the concentration of the complexing agent remained the same as in the second step. NaOH was added to maintain the pH between 10.5 and 11.5, and the reaction proceeded for 10 hours. At this point, the stirring power was reduced to 1.0 kW / m³. 3 (This is lower than the stirring power in the second step), and the reaction continues.

[0193] [Post-processing]

[0194] After rinsing, the product was dried with hot air at approximately 150°C for 24 hours to obtain a nickel-based composite hydroxide (Ni). 0.945 Co 0.04 Al 0.015 (OH)2), which is a precursor of positive electrode active material.

[0195] 2. Preparation of positive electrode active material

[0196] In an oxygen atmosphere, 100 moles of LiOH were mixed with 100 moles of the obtained nickel-based composite hydroxide, and the temperature was raised to 700°C over 5 hours, followed by heat treatment for 10 hours to prepare the final positive electrode active material, nickel-based composite oxide (LiNi). 0.945 Co 0.04 Al 0.015 O2).

[0197] Subsequently, the positive electrode and the battery cell were manufactured in the same manner as in Comparative Example 1.

[0198] Example 1

[0199] In Example 1, the positive electrode active material, positive electrode and battery cell were prepared according to essentially the same method as in Comparative Example 2, except that the temperature was raised to 700°C in an oxygen atmosphere for 8 hours and heat-treated for 7 hours when preparing the positive electrode active material.

[0200] Example 2

[0201] In Example 2, the positive electrode active material, positive electrode and battery cell were prepared according to essentially the same method as in Comparative Example 2, except that the temperature was raised to 700°C in an oxygen atmosphere for 11 hours and heat-treated for 4 hours when preparing the positive electrode active material.

[0202] Evaluation Example 1: Cross-sectional Analysis of Positive Electrode Active Material

[0203] Figure 5 This is a SEM image of the cross-section of the positive electrode active material prepared in Comparative Example 1, cut using FIB. (Reference) Figure 5 In the positive electrode active material prepared in Comparative Example 1, the primary particles were not radially arranged and had a relatively large size and a relatively small aspect ratio.

[0204] Figure 6 The image shows a SEM image of the cross-section of the positive electrode active material prepared in Comparative Example 2, cut using FIB. Figure 7 In order to pass through Figure 6 The image is obtained by contour processing of the primary particles. Figure 7 From left to right, the images show the outlines of primary particles in the entire cross-section of the secondary particles of the positive electrode active material, the outlines of primary particles in the outer portion of the cross-section of the secondary particles, and the outlines of primary particles in the inner portion of the cross-section of the secondary particles. (Reference) Figure 6 and Figure 7 In the positive electrode active material of Comparative Example 2, which introduced a method for preparing a positive electrode active material precursor that differed from that in Comparative Example 1, a portion of the primary particles were arranged radially in the outer portion, but no porous layer was formed.

[0205] Figure 8 The image shows a cross-sectional SEM image of the positive electrode active material according to Example 1, cut using FIB. Figure 9 In order to pass through Figure 8 The image is obtained by contour processing of the primary particles in the image. Similarly, Figure 9 From left to right, the images show the outlines of primary particles within the entire cross-section of a secondary particle, the outlines of primary particles within the outer portion of the cross-section of a secondary particle, and the outlines of primary particles within the inner portion of the cross-section of a secondary particle. (Reference) Figure 8 and Figure 9 It was confirmed that the secondary particles of the positive electrode active material in Example 1 have an internal portion and an external portion. The internal portion has an irregular porous structure, and the primary particles in the external portion are arranged radially. Here, the internal and external portions are distinguished by a 6.51 μm boundary, which is 50% of the diameter of the secondary particles. Since the primary particles at the 50% boundary are included in the internal portion, the secondary particles have a diameter of 13.02 μm, and the internal portion has a diameter of 6.94 μm. The ratio of the radius of the internal portion to the radius of the secondary particles is calculated to be 53.3%, and the ratio of the volume of the external portion to the total volume of the secondary particles is calculated to be 84.9%.

[0206] Figure 10This is a SEM image of the cross-section of the positive electrode active material prepared in Example 2, cut using FIB. Figure 11 In order to pass through Figure 10 The image is obtained by contour processing of the primary particles in the image. Similarly, Figure 11 From left to right, the images show the outlines of primary particles within the entire cross-section of the secondary particles of the positive electrode active material, the outlines of primary particles within the outer portion of the cross-section of the secondary particles, and the outlines of primary particles within the inner portion of the cross-section of the secondary particles. (Reference) Figure 10 and Figure 11 In Example 2, the secondary particles of the positive electrode active material consist of an inner portion having a porous structure and an outer portion in which primary particles are arranged radially. Here, the inner and outer portions are separated by a 6.47 μm boundary, which is 50% of the diameter of the secondary particles. Since the primary particles at the 50% boundary are included in the inner portion, the diameter of the secondary particles is 12.93 μm, and the inner portion has a diameter of 6.94 μm. The ratio of the radius of the inner portion to the radius of the secondary particles is calculated to be 53.7%, and the ratio of the volume of the outer portion to the total volume of the secondary particles is calculated to be 84.5%.

[0207] Evaluation Example 2: Aspect Ratio Distribution Analysis of Primary Particles

[0208] Image analysis program (Image J program) is used for analysis Figure 7 , Figure 9 and Figure 11 The aspect ratio distribution of primary particles in the contour-processed image. Figure 12 A diagram showing the aspect ratio distribution of the primary particles in the "inner portion" of the cross-section of the secondary particles of the positive electrode active materials of Comparative Example 2, Example 1, and Example 2. Figure 13 This is a diagram illustrating the aspect ratio distribution of the primary particles in the "outer portion" of the cross-section of the secondary particles of the positive electrode active materials of Comparative Example 2, Examples 1, and 2. Figure 12 and Figure 13 In the diagram, the horizontal axis represents the aspect ratio of the primary particles, and the vertical axis represents the cumulative quantity ratio.

[0209] Figure 14 To show the passage Figure 12The curve analysis of the aspect ratio distribution of primary particles within the internal portion of secondary particles is based on the number ratios within the aspect ratio range. The dashed line graph represents the number ratio of primary particles with an aspect ratio greater than or equal to approximately 4 within the internal portion of secondary particles; the brick-shaped bar graph represents the number ratio of primary particles with an aspect ratio greater than 2.5 and less than 4; and the black bar graph represents the number ratio of primary particles with an aspect ratio less than or equal to approximately 2.5. The dashed line graph corresponds to the right vertical axis, and the brick-shaped bar graph and the black bar graph correspond to the left vertical axis.

[0210] Figure 15 To show the passage Figure 13 The curve analysis of the aspect ratio distribution of primary particles in the outer portion of secondary particles is based on the number ratio of primary particles within the aspect ratio range. The dashed line graph represents the number ratio of primary particles in the outer portion of secondary particles with an aspect ratio greater than or equal to approximately 4; the shaded bar graph represents the number ratio of primary particles with an aspect ratio greater than 2.5 and less than 4; and the black bar graph represents the number ratio of primary particles with an aspect ratio less than or equal to approximately 2.5. The dashed line graph corresponds to the right vertical axis, and the shaded and black bar graphs correspond to the left vertical axis.

[0211] refer to Figure 15 The external portion of Comparative Example 2 was compared with the external portions of Examples 1 and 2. In Comparative Example 2, a method for preparing the positive electrode active material precursor, different from the method for preparing the positive electrode active material precursor in Comparative Example 1, was introduced. A portion of the primary particles were arranged radially. In the external portion of the secondary particles in Comparative Example 2, the proportion of primary particles with an aspect ratio greater than or equal to 4 was 15% (dashed line diagram). However, in Example 1, the proportion of primary particles with an aspect ratio greater than or equal to 4 was 18%, and in Example 2, the proportion of primary particles with an aspect ratio greater than or equal to 4 was 25%, which is much higher than the proportion of primary particles with an aspect ratio greater than or equal to 4 in Comparative Example 2. Furthermore, in Comparative Example 2, the proportion of primary particles with an aspect ratio less than or equal to about 2.5 in the outer portion of the secondary particles was 57% (black bar graph), but in Example 1, the proportion of primary particles with an aspect ratio less than or equal to about 2.5 in the outer portion of the secondary particles was 54%, and in Example 2, the proportion of primary particles with an aspect ratio less than or equal to about 2.5 in the outer portion of the secondary particles was 41%, which is lower than the proportion of primary particles with an aspect ratio less than or equal to about 2.5 in the outer portion of the secondary particles in Comparative Example 2.

[0212] Therefore, compared to Comparative Example 2, Examples 1 and 2 exhibit a high proportion of primary particles with a large aspect ratio in the outer portion of the secondary particles, but a low proportion of primary particles with a small aspect ratio. For example, Examples 1 and 2 satisfy the condition that the proportion of primary particles with an aspect ratio greater than or equal to 4 in the outer portion of the secondary particles is greater than or equal to 18%, but Comparative Example 2 shows that the proportion of primary particles with an aspect ratio greater than or equal to 4 in the outer portion of the secondary particles is less than 18%. Furthermore, Examples 1 and 2 exhibit that the proportion of primary particles with an aspect ratio less than or equal to 2.5 in the outer portion of the secondary particles is less than or equal to 54%, but Comparative Example 2 shows that the proportion of primary particles with an aspect ratio less than or equal to 2.5 in the outer portion of the secondary particles is greater than 54%.

[0213] In addition, based on Embodiment 1 and Embodiment 2, Figure 14 and Figure 15 In comparison, primary particles with a large aspect ratio are more distributed in the outer part of the secondary particles rather than in the inner part of the secondary particles.

[0214] In other words, the positive electrode active materials prepared in Examples 1 and 2 have a structure in which primary particles with a large aspect ratio are more distributed on the outer portion of the secondary particles rather than in the inner portion, and primary particles with a very large aspect ratio (e.g., 4 or greater) are present at a high ratio (e.g., 18% or greater). Accordingly, lithium ions can move more easily in the positive electrode active material, greatly reducing the stress caused by the contraction and expansion of the positive electrode active material during repeated charging and discharging.

[0215] Accordingly, rechargeable lithium-ion battery cells can achieve high capacity and improve initial charge / discharge efficiency and cycle life characteristics, and the experimental results will be described later.

[0216] Evaluation Example 3: Cross-sectional area analysis of primary particles

[0217] Regarding the cross-sections of the positive electrode active materials in Comparative Example 1 and Examples 1 and 2, after contour processing of the primary particles, the area distribution of the cross-sections of the primary particles was analyzed using an image analysis program (Image J program), and the results are shown in... Figure 16 In. Figure 16 In the diagram, the horizontal axis represents the cross-sectional area of ​​the primary particles, and the vertical axis represents the quantity ratio.

[0218] Figure 17 This is a graph showing the cross-sectional area distribution of primary particles, where black bars represent cross-sectional areas less than 0.1 μm. 2 The ratio of primary particles, the shaded bar graph represents the cross-sectional area of ​​0.1 μm.2 Up to 0.3μm 2 The ratio of primary particles, and the dashed line graph indicates a cross-sectional area greater than 0.3 μm. 2 The ratio of the number of primary particles. The brick-shaped bar chart and the black bar chart correspond to the left vertical axis, and the dashed line chart corresponds to the right vertical axis.

[0219] refer to Figure 17 In Comparative Example 1, the cross-sectional area was less than 0.1 μm. 2 The proportion of primary particles was 37%, but in Example 1, the cross-sectional area was less than 0.1 μm. 2 The primary particle count was 70%, and in Example 2, the cross-sectional area was less than 0.1 μm. 2 The proportion of primary particles was 78%, which is significantly higher than that of Comparative Example 1, where the cross-sectional area was less than 0.1 μm. 2 The ratio of primary particles. Additionally, in Comparative Example 1, the cross-sectional area of ​​the primary particles was greater than 0.3 μm. 2 The proportion of primary particles was approximately 33%, but in Example 1, the cross-sectional area of ​​the primary particles was greater than 0.3 μm. 2 The number ratio of primary particles is approximately 4%, and in Example 2, the cross-sectional area of ​​the primary particles is greater than 0.3 μm. 2 The proportion of primary particles was approximately 3%, significantly lower than that of primary particles in Comparative Example 1, where the cross-sectional area of ​​the primary particles was greater than 0.3 μm. 2 The ratio of the number of primary particles.

[0220] Thus, the positive electrode active material according to Examples 1 and 2 has a structure in which a large number of primary particles with small cross-sectional areas are distributed, and is therefore expected to improve initial charge / discharge efficiency, capacity and cycle life characteristics.

[0221] Evaluation Example 4: Evaluation of Initial Charge Capacity, Initial Discharge Capacity, and Initial Charge / Discharge Efficiency

[0222] At 25°C, the battery cells according to Comparative Examples 1 and 2, as well as Examples 1 and 2, were charged to an upper limit voltage of 4.25V at a constant current of 0.2C, charged to 0.05C at a constant voltage, and then discharged to a discharge cutoff voltage of 3.0V at a constant current of 0.2C. This was performed as the initial charge and discharge, and the results are shown in... Figure 18 middle.

[0223] refer to Figure 18Compared to Comparative Example 1, Comparative Example 2, as well as Examples 1 and 2 (where a positive electrode active material including radially arranged primary particles was applied), exhibited significantly increased initial charge capacity, initial discharge capacity, and initial charge / discharge efficiency (i.e., formation efficiency). Furthermore, compared to Comparative Example 2, the primary particles with an aspect ratio greater than or equal to 4 were fully developed in the outer portion of the secondary particles, and the cross-sectional area of ​​the primary particles was less than 0.1 μm across the entire cross-section. 2 Examples of fully developed primary particles demonstrate a slight increase in initial charge capacity and initial discharge capacity, as well as an additional increase in initial charge / discharge efficiency.

[0224] Evaluation Example 5: Evaluation of High Temperature Cycling Life

[0225] First, the battery cells according to Comparative Examples 1 and 2, as well as Examples 1 and 2, were charged and discharged as in Evaluation Example 4. Then, at 45°C, at a voltage ranging from 3.0V to 4.3V, and at 1C, the charge and discharge cycles were repeated 50 times. The cycle life characteristics were then evaluated, and the results are shown in... Figure 19 middle. Figure 19 The initial discharge capacity, the discharge capacity at 50 cycles, and the ratio of the discharge capacity at 50 cycles to the initial discharge capacity, which is the capacity retention rate at 50 cycles, are shown.

[0226] refer to Figure 19 Compared to Comparative Examples 1 and 2, Examples 1 and 2 both exhibited improved initial discharge capacity, discharge capacity at 50 cycles, and capacity retention at 50 cycles. In particular, Comparative Example 2 used a positive electrode active material in which secondary particles of primary particles were radially arranged; however, the aspect ratio distribution and / or cross-sectional area distribution of the primary particles differed from those in Examples 1 and 2, ultimately exhibiting degraded initial charge / discharge efficiency and cycle life characteristics. However, in the secondary particles of the positive electrode active material prepared in Examples 1 and 2, the aspect ratio distribution and / or cross-sectional area distribution of the primary particles can be controlled to improve the initial charge / discharge efficiency of the rechargeable lithium-ion battery cell and achieve high capacity and enhanced high-temperature cycle life characteristics.

[0227] Although preferred embodiments have been described in detail above, the scope of the invention is not limited thereto. Furthermore, it should be understood that various modifications and improvements made by those skilled in the art using the basic concepts defined in the claims also fall within the scope of the invention.

Claims

1. A positive electrode active material for a rechargeable lithium battery, comprising: A lithium-nickel composite oxide, wherein the positive electrode active material is in the form of secondary particles, wherein multiple primary particles are aggregated within the secondary particles, and at least a portion of the primary particles are radially arranged. The secondary particle includes an inner portion and an outer portion. The inner portion of the secondary particle is a region surrounded by a point located at 50 ± 5% of the total distance from the center of the secondary particle to its surface, and is the region where the primary particles and pores are irregularly arranged. The outer portion of the secondary particle is the remaining region surrounding the inner portion, wherein at least a portion of the primary particles are arranged radially in the outer portion. The number of primary particles with an aspect ratio greater than or equal to 4 in the outer portion of the secondary particles is greater than or equal to 18%.

2. The positive electrode active material for a rechargeable lithium battery according to claim 1, wherein... The proportion of primary particles with an aspect ratio greater than or equal to 4 in the outer portion of the secondary particles is 18% to 45%.

3. The positive electrode active material for a rechargeable lithium battery according to claim 1, wherein... The number of primary particles with an aspect ratio less than or equal to 2.5 in the outer portion of the secondary particles is less than or equal to 54%.

4. The positive electrode active material for a rechargeable lithium battery according to claim 1, wherein... The number of primary particles with an aspect ratio greater than or equal to 4 in the outer portion of the secondary particles is three times or greater than the number of primary particles with an aspect ratio greater than or equal to 4 in the inner portion of the secondary particles.

5. The positive electrode active material for a rechargeable lithium battery according to claim 1, wherein... The proportion of primary particles with an aspect ratio greater than or equal to 4 in the internal portion of the secondary particles is 5% to 15%.

6. The positive electrode active material for a rechargeable lithium battery according to claim 1, wherein... The proportion of primary particles with an aspect ratio less than or equal to 2.5 in the internal portion of the secondary particles is less than or equal to 71%.

7. The positive electrode active material for a rechargeable lithium battery according to claim 1, wherein... The cross-sectional area of ​​the secondary particles is less than 0.1 μm. 2 The number ratio of the primary particles is greater than or equal to 70%.

8. The positive electrode active material for a rechargeable lithium battery according to claim 7, wherein... In the cross-section of the secondary particle, the cross-sectional area is less than 0.1 μm. 2 The number ratio of the primary particles is 70% to 90%.

9. The positive electrode active material for a rechargeable lithium battery according to claim 7, wherein... In the cross-section of the secondary particle, the cross-sectional area is greater than 0.3 μm. 2 The number ratio of the primary particles is less than or equal to 5%.

10. The positive electrode active material for a rechargeable lithium battery according to claim 1, wherein... The average particle size of the secondary particles is 8 μm to 20 μm.

11. The positive electrode active material for a rechargeable lithium battery according to claim 1, wherein... The lithium-nickel composite oxide is represented by chemical formula 1: [Chemical Formula 1] Li a1 Ni x1 M 1 y1 M 2 1-x1-y1 O 2-z X z , in, In chemical formula 1, 0.9 ≤ a1 ≤ 1.8, 0.3 ≤ x1 ≤ 1, 0 ≤ y1 ≤ 0.7, and 0 ≤ z ≤ 0.1, M 1 and M 2 Each element is independently selected from at least one element chosen from Al, B, Ba, Ca, Ce, Co, Cr, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, and Zr, and X is selected from at least one element chosen from F, P, and S.

12. A method for preparing a positive electrode active material for a rechargeable lithium battery according to any one of claims 1-11, comprising: A positive electrode active material precursor comprising a nickel-based composite hydroxide and a lithium raw material are mixed, and the resulting product is subjected to heat treatment to obtain a positive electrode active material for a rechargeable lithium battery according to any one of claims 1-11. The heat treatment includes a heating process and a holding process, and the heating time is longer than the holding time.

13. The method of claim 12, wherein The heating time is 6 to 16 hours. The heat preservation time is from 1 hour to 9 hours, and The heating time is longer than the heat preservation time.

14. The method of claim 12, wherein The ratio of heating time to holding time is 1.1:1 to 10:

1.

15. The method of claim 12, wherein The heat treatment is carried out at 600°C to 900°C.

16. A rechargeable lithium battery, comprising: The positive electrode comprises the positive electrode active material according to any one of claims 1 to 11 or the positive electrode active material prepared by the method according to any one of claims 12 to 15. negative electrode, and Electrolytes.

Citation Information

Patent Citations

  • Cathode active material for secondary battery, preparation method therefor, and secondary battery comprising same

    CN107534140A